Production, marketing, and consumption of small ruminants in Mali - Dembele, Bandiougou; Kassie, Girma; Fall, Abdou (Institut d'Economie Rurale, 2022)
This report contains information about Mali's agricultural sector, and breeds of small ruminants in Mali, reproduction system, production parameters of small ruminants in traditional system, constraints to the production systems and the role of small ruminants in the livelihoods of smallholder producers.